Correlating Factors to Adolescent Sexual Behavior at SMP Negeri X Medan Belawan 2018 - Sinaga, Mariana; Santoso, Heru; Sinaga, Lia Rosa Veronika (Sari Mutiara Indonesia University Press, 2018)
Sexual behavior is the behavior which is stimulated by sexual desire with the opposite sex or with same sex.it is started from the feeling of attraction to a date, holding hands,embracing,touching parts of the body,patting,oral sex,masturbation,kissing, and committing sexual intercouse among adolescents.These are correlated with same factors such as knowledge,self-control,parents’ Role,peers’Role, and information media. The objective of this research was to find out some factors which were correlated with adolescent’ sexual behavior at SMP Negeri X , Medan Belawan,in 2018. The research used quantitative method with cross sectional design. The samples were 85 respondents,taken by using purposive random sampling technique. The data were gathered by using questionnaires and analyzed by using univariate analysis and bivariate analysis with Chi Square test with interval confidence (CI=95%) and the confidence level of =0.05. The result of the research showed that there was the correlation of knowledge (p=0.001),parents’role (p=0.001),self-control (p=0.001),and information media (p=0.004) with adolescents’sexual behavior at SMP Negeri X,Medan Belawan .It is recommended that parents not consider sexual education as taboo for their children; on the other hand,it is very useful for them.Adolescents should be wise in using information media and avoid the exposure to pornography from peers who like to persuade to commit sexual act. Therefore, the school management and teachers should prevent the students from sexual behavior by providing education on sex so that adoslescents can have sel-control in preventing from sexual behavior.